ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ø§Ø³ØªÙ…Ø§Ø¹ Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ± Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Maulidati, Maulidati ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2020)
Listening skills are one of the most important language skills and must be learned by all students, and it is the most important language art off all time in teaching Arabic to speakers of other language. These language skills occupy first place in language skills. Then speaking, reading and writing skills. Listening is an important factor in communication process, because it always playts an important role in teching and learning throughout the age, but listening skills are often ignored bechouse everyone assumed that students can listen on their own. They just listen if asked, but this opinion eventually changes. Research has proven that listening skills are process that requires practice and learning